Cardiac Fibroblast GRK2 Deletion Enhances Contractility and Remodeling Following Ischemia/Reperfusion Injury - Woodall, Meryl C. (Circ Res, 2016)
RATIONALE: G protein-coupled receptor kinase 2 (GRK2) is an important molecule upregulated after myocardial injury and during heart failure. Myocyte-specific GRK2 loss before and after myocardial ischemic injury improves cardiac function and remodeling. The cardiac fibroblast plays an important role in the repair and remodeling events following cardiac ischemia; the importance of GRK2 in these events has not been investigated. OBJECTIVE: The aim of this study is to elucidate the in vivo implications of deleting GRK2 in the cardiac fibroblast after ischemia/reperfusion (I/R) injury. METHODS AND RESULTS: We demonstrate, using Tamoxifen inducible, fibroblast-specific GRK2 knockout mice, that GRK2 loss confers a protective advantage over control mice after myocardial I/R injury. Fibroblast GRK2 knockout mice presented with decreased infarct size and preserved cardiac function 24 hours post-I/R as demonstrated by increased ejection fraction (58.1±1.8% vs. 48.7±1.2% in controls, p<0.0005). GRK2 fibroblast knockout mice also had decreased fibrosis and fibrotic gene expression. Importantly, these protective effects correlated with decreased infiltration of neutrophils to the ischemia site and decreased levels of TNFα expression and secretion in GRK2 fibroblast knockout mice. CONCLUSIONS: These novel data showing the benefits of inhibiting GRK2 in the cardiac fibroblast adds to previously published data showing the advantage of GRK2 ablation and reinforces the therapeutic potential of GRK2 inhibition in the heart after myocardial ischemia.